2018
DOI: 10.1093/jn/nxy003
|View full text |Cite
|
Sign up to set email alerts
|

Accretion of Fat-Free Mass Rather Than Fat Mass in Infancy Is Positively Associated with Linear Growth in Childhood

Abstract: Background:We have previously shown that fat-free mass (FFM) at birth is associated with height at 2 y of age in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…This study therefore breaks new ground in explaining the possible mechanism by which early life weight gain relates to childhood fatness. In our previous analyses, postnatal FM accretion had a positive association with linear growth from 1 to 5 years 41 . However, studies conducted in middle 57 - and high 58 - income countries have found that infancy and childhood FM is associated with markers of cardio-metabolic status in children and adolescents.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…This study therefore breaks new ground in explaining the possible mechanism by which early life weight gain relates to childhood fatness. In our previous analyses, postnatal FM accretion had a positive association with linear growth from 1 to 5 years 41 . However, studies conducted in middle 57 - and high 58 - income countries have found that infancy and childhood FM is associated with markers of cardio-metabolic status in children and adolescents.…”
Section: Discussionmentioning
confidence: 67%
“…This supports the hypothesis of “fetal programming” of later health, which may reflect the tracking of fetal FFM into the childhood period. In the same cohort, we have previously shown that FFM at birth was a positive predictor of height 46 and cognitive development at 2 years 47 and linear growth from 1 to 5 years of age 41 . Collectively, these results indicate that higher prenatal growth, if mainly driven by lean mass, benefits health and development during childhood.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations